Impacts of the quinone-functionalized biochar on anaerobic digestion: Beyond the redox property of biochar - Qian Jiang; Wentao Zhou; Yue Chen; Zhenglong Peng; Chengcheng Li (PLoS ONE, 2025)
Recent developments in biochar materials have led to renewed interest in biochar modification for environmental applications, however, much uncertainty still exists about the impact of engineered biochar on a given biotechnological process. The redox properties of biochar were considered to be the key property for enhancing the methanogenic process, and the redox activity of biochar was closely related to the type and amount of oxygen-containing functional groups, especially quinone groups. Therefore, anthraquinone-2-sulfonate (AQS) was immobilized on algal biochar (ABC) by surface doping method, and the impacts of the quinone-functionalization process on algal biochar for regulating methane production were investigated in this study. Results showed that the immobilization capacity of AQS on ABC (ABC-AQS) reached 0.289 mmol/g. The acidogenesis rate was improved by 26.3% with the addition of ABC-AQS during anaerobic digestion test. However, methane production was inhibited rather than enhanced by the ABC-AQS, which could be attributed to the strong acid treatment stage involved in the biochar modification process. pH interferences, the generation and/or dissolution of inhibitory substances, and the release of Zn2+ should be the major mechanisms of microbial inhibition by ABC-AQS. The findings of this study give us an important clue that when designing a biochar modification procedure for anaerobic digestion, attentions should be paid to the possible influences of chemical side reactions during biochar modification process on subsequent microbial metabolism, which would be valuable in designing engineered biochar for practical applications.